DESAIN PEMBELAJARAN BAHASA ARAB BERBASIS SOCIAL-LEARNING NETWORK EDMODO Penelitian dan Pengembangan di Jurusan PBA FITK UIN Maulana Malik Ibrahim Malang) - ABDUL BASID (Prosiding Konferensi Nasional Bahasa Arab, 2015)
One of developing types of learning and teaching Arabic in UIN Maulana Malik Ibrahim Malang is web-based learning and teaching. This learning and teaching uses social-learning network, such as edmodo.com. This study is research & development. Therefore, this study purposes to find, to formulate, to fix, to develop, to produce and to examine a product, a model, a strategy, a method, and a procedure. The findings of this study are: 1) the handbook of teaching and learning Arabic based sosial-learning network edmodo. It contains of steps to create account in edmodo for students, teachers, and parents; steps to make a group or class; and steps to post alert, note, assignment, kuis and all; 2) the handbook of teaching and learning based sosial-learning network edmodo is usefull and effective to improve teaching and learning Arabic. It can be detected from their score in some subjects, such as writing, reading, vocabulary, and structure.Keywords: Design, social-learning network edmodo, Arabic, product.